Tolerância zero ou eficácia nula? Políticas públicas e regulamentos desportivos para combater o match-fixing - Cima, C.; Moriconi, M. (Sociologia, Problemas e Práticas, 2022)
Through semi-structured interviews and documentary analysis this article assesses and exposes how the “zero tolerance” policy implemented by UEFA, the European football’s governing body, is inefficient in inducing compliance in football players, at the level of match-fixing practices. The excessive emphasis on individual ethical, the externalization of the phenomenon as an organized crime problem and the reluctance to admit internal governance failures are the main explanatory reasons. The article claims that football regulation should move from a logic of compliance to enforcement politics.